Optimum Design for Cathode Layout Arrangement of IGCT - 程银华; 陈芳林; 彭文华 (Kongzhi Yu Xinxi Jishu)
The gate-cathode structure and operation principle of IGCT are analyzed simply. Then a novel finger arrangement manner for cathode layout, finger partition composite arrangement, is supplied based on the original uniform rectangle arrangement and uniform circle arrangement. In this way, IGCT cathode effective area is expanded and current capacity is enhanced; furthermore, thermal resistance can be decreased while gate current channel is improved.